IOS, Capital Structure and Growth: The Value Of Banks In Indonesia - Utami, Vika Dwi; Sari, Asih Purwana; Nopiana, Puspita Rama (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of investment opportunity set (IOS), capital structure, and firm growth on firm value using a population of 47 banking sector companies listed on the Indonesia Stock Exchange during the period from 2017 to 2021. The study utilizes purposive sampling method, resulting in a sample of 14 companies for the research. This research falls under the category of descriptive research with a quantitative approach, using secondary data obtained from the financial reports of the companies listed on the Indonesia Stock Exchange (IDX). Hypothesis testing in this research employs the multiple linear regression analysis method, descriptive analysis, factor analysis, classical assumptions, determination coefficient, t-test, and F-test. The results of this research show that partially, capital structure and firm growth have a positive and significant impact, while investment opportunity set has a positive but not significant impact on firm value. With an Adjusted R Square value of 0.571 or 51.1%, this indicates that the contribution of investment opportunity set (IOS), capital structure, and firm growth to firm value is 51.1%, while the remaining 42.9% is explained by other factors.